Vague language - Joanna Channell (Oxford Univ. Press, 1994)
The book shows how English provides its speakers with a great variety of ways of being vague. It applies principles of pragmatics to the analysis of vague expressions, describing both the linguistic forms and the pragmatic consequences of their use